Entrepreneurial Team Cognition: A Review. (April 2015) - de Mol, Eva; Khapova, Svetlana N.; Elfring, Tom; Grégoire, Denis A.; Cornelissen, Joep; Dimov, Dimo; van Burg, Elco
<x xml:space="preserve">Abstract</x> Entrepreneurial team scholars highlight the importance of studying entrepreneurial team cognition in gaining a better understanding of why some entrepreneurial teams are capable of developing teamwork leading to successful entrepreneurial outcomes while others are not. However, in the absence of a clear definition of entrepreneurial team cognition, researchers continue to employ a vast diversity of potentially related concepts. To bring clarity to this fragmented area of research, the authors performed a systematic literature review of papers concerned with entrepreneurial team cognition published in the leading management and entrepreneurship journals over the past 20 years. This review was guided by two main research questions: (a) what is entrepreneurial team cognition, and (b) how does entrepreneurial team cognition interact with inputs, processes and outcomes. Based on the published literature, key properties of the concept are identified, and an overarching definition of entrepreneurial team cognition composed of these properties is introduced. Next, the review outlines how entrepreneurial team cognition interacts with other variables within a comprehensive input‐mediator‐output framework. Finally, the review addresses how future research can build on the proposed definition and framework to advance the theoretical depth and empirical investigation of entrepreneurial team cognition.